A Cross-Sectional Satisfaction Survey of 845 Traffic Accident Patients Treated with Korean Medicine - No H. Kim; Yoon J. Lee; Chang Y. Suh; Gi B. Lee; Kyu J. Yang; Tae-Gyu Kim; Yu-Mi Gi; Mijung Kwon; In-Hyuk Ha (MEDrang Inc., 2018)
Background We conducted a cross-sectional study to analyze the pain characteristics and satisfaction scoresin traffic accident (TA) patients seeking Korean medicine treatment. Methods A survey was conducted in 845 outpatients who visited 10 Korean medicine institutions due to TA-associated symptoms from February 25th, 2016 to March 9th, 2016. The questionnaire included information about patient sociodemographic characteristics, accident circumstance details, pain levels, treatment methods, satisfaction and pre-existing musculoskeletal disorders. All statistical analyses were performed using STATA 14.0. Results A total 754 of the 845 respondents had experienced acute pain of onset within 1-2 days. Pain in the neck or low back was most common, and low back pain (LBP) was more prevalent in pedestrian-vehicle accident cases. Patients showed highest satisfaction with pharmacopuncture treatment, followed by acupuncture and Chuna manual therapy. Although treatments were not completed at the time of the survey, the majority of patients were satisfied with the Korean medicine treatments they received and indicated their intent to reuse this treatment in the future. The degree of pain reduction after treatment was a factor that influenced patient satisfaction with and intention to reuse Korean medicine. Conclusions This study determined the characteristics and status of TA patients using Korean medicine andsuggests the need for further more inclusive studies.